Detecting propagandistic poster title: a machine learning approach - Mahmood, Riaz; Shah, Intiajul Alam; Hassan, Tasnimul; Abdullah, Hasan; Mubassir, Taskin Mohammad (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2024.